1994
DOI: 10.1007/bf00180547
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose hydrocortisone infusion attenuates the systemic inflammatory response syndrome

Abstract: There is increasing evidence that the hypercortisolemia in inflammatory diseases suppresses the elaboration of proinflammatory cytokines, thus protecting the host from its own defence reactions. In severe sepsis and septic shock cortisol levels are usually elevated, but some patients may have relative adrenal insufficiency. This may contribute to the overwhelming systemic inflammatory response syndrome. We evaluated the impact of low-dose hydrocortisone infusion (10 mg/h) on the course of the systemic inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
9

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 23 publications
5
90
0
9
Order By: Relevance
“…Release of cortisol or administration of glucocorticoids can attenuate this response and thus prevent cardiovascular collapse. 3,5,7 Cortisol is also proposed to play a vital role in maintaining hemodynamic stability through other mechanisms that are beyond the scope of this paper, including potentiating transmembrane calcium currents, increasing b-receptor sensitivity to catecholamines, reversing downregulation or inhibiting degradation of b-receptors, increasing the density of b-receptors or inhibiting nitric oxide synthase expression. 12 Indeed, the clinical feature that is most often linked with relative adrenal insufficiency in critically ill patients in the intensive care unit is hemodynamic instability and shock.…”
Section: Corticosteroid Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Release of cortisol or administration of glucocorticoids can attenuate this response and thus prevent cardiovascular collapse. 3,5,7 Cortisol is also proposed to play a vital role in maintaining hemodynamic stability through other mechanisms that are beyond the scope of this paper, including potentiating transmembrane calcium currents, increasing b-receptor sensitivity to catecholamines, reversing downregulation or inhibiting degradation of b-receptors, increasing the density of b-receptors or inhibiting nitric oxide synthase expression. 12 Indeed, the clinical feature that is most often linked with relative adrenal insufficiency in critically ill patients in the intensive care unit is hemodynamic instability and shock.…”
Section: Corticosteroid Physiologymentioning
confidence: 99%
“…2,3,5 Some studies of glucocorticoid treatment in critically ill adults have shown benefit, with faster reversal of shock and reduction in mortality. 3,[5][6][7][8] Recently, increasing evidence supports the existence of relative adrenal insufficiency in ill newborns, but, similar to other ill populations, there remains no general consensus on which patients should be tested, which tests to use and how to interpret them, which patients should be treated or how they should be treated. 9 The following discussion is an overview of corticosteroid physiology, relative adrenal insufficiency in critically ill populations and evidence of its existence in newborn infants, with proposed underlying mechanisms, diagnostic criteria, consequences and recommendations for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in patients with septic shock have demonstrated that hydrocortisone infusion produces a significant decrease in the circulating levels of proteins dependent upon the transcription factor nuclear factor-kB, such as phospholipase A 2 , IL-6 and -8, and soluble E-selectin [29]. The suppression of the treatment provokes a rebound effect in most of these mediators, which highlights the shortacting anti-inflammatory action of hydrocortisone and the need to provide prolonged treatment in order to achieve a durable anti-inflammatory effect [29,44]. As acknowledged by the authors of the ARDS Network trial, rapid tapering and removal of methylprednisolone probably contributed to the deterioration in Pa,O 2 /FI,O 2 ratio and higher rate of intubation in the treatment arm [41].…”
Section: Role Of Glucocorticosteroids In Severe Pneumoniamentioning
confidence: 99%
“…Low-dose hydrocortisone infusions may attenuate this systemic inflammatory response, as judged by clinical signs and inflammatory markers (2)(3)(4). Two double-blind, single-center trials demonstrated that stress doses of hydrocortisone reversed septic shock, as defined by cessation of vasopressor therapy.…”
Section: Introductionmentioning
confidence: 99%